Production and characterization of monoclonal antibody to recombinant chicken IL-2 - LI Zeng-kui; GONG Hui; CHEN Ji-gang; WU Jian-xiang; ZHOU Ji-yong (浙江大学学报. 农业与生命科学版, 2004)
Four hybridoma cell lines named as 1A12, 4A3, 3E7 and 4E1, secreting monoclonal antibody (MAb) against chicken IL-2 were produced by fusing mouse myeloma cells (SP2/0) with spleen cells from BALB/c immunized with the purified recombinant chicken IL-2 protein. The four MAbs were identified as follows: The ELISA titers were 5.12× 105, 1.02×106, 2.56×105 and 4.09×106, respectively. All the Mabs failed into type IgG1. Western-blot analysis showed that the four MAbs could react with chicken IL-2.